1990
DOI: 10.1097/00000658-199011000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Positive Results of Combined Therapy of Surgery and Intraperitoneal Hyperthermic Perfusion for Far-advanced Gastric Cancer

Abstract: To evaluate the clinical efficacy of intraperitoneal hyperthermic perfusion (IPHP) for far-advanced gastric cancer, particularly with peritoneal seeding, we investigated the survival times of 59 patients who underwent distal subtotal gastrectomy, total gastrectomy, or total gastrectomy combined with concomitant resection of some of the remaining intra-abdominal organs. In all the 30 patients given IPHP, no cancer cells were present posthyperthermically in the lavage from the Douglas pouch. The 30 patients give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 7 publications
0
43
0
Order By: Relevance
“…However, there are no PC treatment approved by regulatory agencies, and the development of new therapies to manage this life-threatening condition could fulfill an unmet medical need. In this context, several Phase I/II clinical studies in gastric cancer (1)(2)(3), mesothelioma (4), colorectal (5), or ovarian carcinoma (6) have shown promising results in treating macroscopic PC with cytoreductive surgery and residual PC with hyperthermic intraperitoneal chemotherapy (HIPEC) (7). The rationale for this treatment is based on experimental studies showing that drug penetration is limited to a few cell layers under the surface of the tumor (8), and consequently, intraperitoneal chemotherapy must be immediately administered after the cytoreductive surgery in order to achieve the maximal cytotoxic activity on residual tumor cells before they get trapped in the postoperative fibrin adhesions (9).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no PC treatment approved by regulatory agencies, and the development of new therapies to manage this life-threatening condition could fulfill an unmet medical need. In this context, several Phase I/II clinical studies in gastric cancer (1)(2)(3), mesothelioma (4), colorectal (5), or ovarian carcinoma (6) have shown promising results in treating macroscopic PC with cytoreductive surgery and residual PC with hyperthermic intraperitoneal chemotherapy (HIPEC) (7). The rationale for this treatment is based on experimental studies showing that drug penetration is limited to a few cell layers under the surface of the tumor (8), and consequently, intraperitoneal chemotherapy must be immediately administered after the cytoreductive surgery in order to achieve the maximal cytotoxic activity on residual tumor cells before they get trapped in the postoperative fibrin adhesions (9).…”
Section: Introductionmentioning
confidence: 99%
“…Fujimoto et al (54) reported a prospective study of 59 patients, 32 of whom had advanced GC without PC who underwent curative surgery. The 2-year survival of the 10 patients who received HIPEC was significantly higher than that of the 20 patients who did not (56.5% vs. 12.9%, P=0.01).…”
Section: Crs + Hipec Clinical Experience: Promising Resultsmentioning
confidence: 99%
“…Since then, various Asian groups have gone on to investigate the use of HIPEC in the prophylactic setting [21,25,26,[83][84][85][86][87]. All of them have provided evidence to show that HIPEC in the prophylactic setting can reduce the incidence of peritoneal recurrence and improve survival.…”
Section: Discussionmentioning
confidence: 99%
“…The abstracts of these 145 articles were reviewed carefully and a further 42 articles had full text review. Ultimately, 17 articles were included in this review and summarized in Table 1 [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Of the 17 articles included in the review, 1 was a systematic review, 1 was a randomized controlled trial, 11 were prospective studies (7 case series, 4 case controls and 1 prospective randomized trial) and the remaining 4 were retrospective studies.…”
Section: Study Selectionmentioning
confidence: 99%